2020
DOI: 10.1007/s12325-020-01566-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Aripiprazole and Olanzapine Multiple-Dose Treatment in a Randomised Crossover Clinical Trial in Healthy Volunteers: Association with Pharmacogenetics

Abstract: Introduction Aripiprazole and olanzapine are atypical antipsychotics. Both drugs can induce metabolic changes; however, the metabolic side effects produced by aripiprazole are more benign. The aim of the study was to evaluate if aripiprazole and olanzapine alter prolactin levels, lipid and glucose metabolism and hepatic, haematological, thyroid and renal function. Methods Twenty-four healthy volunteers received a daily oral dose of 10 mg aripiprazole and 5 mg olanzapine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 64 publications
(86 reference statements)
0
30
0
Order By: Relevance
“…It is hypothesized that additional drug-mediated mechanisms are partially responsible for antipsychotic-induced weight gain ( Himmerich et al, 2015 ). Olanzapine-induced weight gain was observed even after only 5 days acute treatment in healthy volunteers ( Koller et al, 2021 ). Other studies observed a 0.9 kg per month weight gain in schizophrenic patients treated with olanzapine ( Lieberman et al, 2005 ) or a weight gain of 13.9 kg in patients after 1 year of olanzapine treatment ( Kahn et al, 2008 ).…”
Section: Metabolic Effects Of Risperidone Olanzapine and Aripiprazolementioning
confidence: 99%
See 4 more Smart Citations
“…It is hypothesized that additional drug-mediated mechanisms are partially responsible for antipsychotic-induced weight gain ( Himmerich et al, 2015 ). Olanzapine-induced weight gain was observed even after only 5 days acute treatment in healthy volunteers ( Koller et al, 2021 ). Other studies observed a 0.9 kg per month weight gain in schizophrenic patients treated with olanzapine ( Lieberman et al, 2005 ) or a weight gain of 13.9 kg in patients after 1 year of olanzapine treatment ( Kahn et al, 2008 ).…”
Section: Metabolic Effects Of Risperidone Olanzapine and Aripiprazolementioning
confidence: 99%
“…Olanzapine is also known to increase the risk of developing type II diabetes ( Lambert et al, 2006 ; Koller et al, 2021 ). Its M3 receptor antagonism causes an alteration in glucose control and insulin response, and the blockade of the H1 receptor favors the development of insulin resistance.…”
Section: Metabolic Effects Of Risperidone Olanzapine and Aripiprazolementioning
confidence: 99%
See 3 more Smart Citations